2016
DOI: 10.1021/acs.jafc.6b02291
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Two Critical Residues in Inulin Fructotransferase (DFA III-Producing) Thermostability from Arthrobacter sp. 161MFSha2.1

Abstract: Inulin fructotransferase (IFTase) is an important enzyme that produces di-d-fructofuranose 1,2':2,3' dianhydride (DAF III), which is beneficial for human health. Present investigations mainly focus on screening and characterizing IFTase, including catalytic efficiency and thermostability, which are two important factors for enzymatic industrial applications. However, few reports aimed to improve these two characteristics based on the structure of IFTase. In this work, a structural model of IFTase (DFA III-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Several studies have reported that combinations of different mutants often further improve the thermostability of enzymes. ,,, The S361R/S444E/G415P mutant was obtained by combining S361R/S444E with G415P. The t 1/2 at 60 °C of triple-mutant enzyme increased remarkably by 19.7-fold compared to the wild-type enzyme, suggesting that G415P and S361R/S444E had an unexpected synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that combinations of different mutants often further improve the thermostability of enzymes. ,,, The S361R/S444E/G415P mutant was obtained by combining S361R/S444E with G415P. The t 1/2 at 60 °C of triple-mutant enzyme increased remarkably by 19.7-fold compared to the wild-type enzyme, suggesting that G415P and S361R/S444E had an unexpected synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Figure d represents the space-filling model of M1’s structure, where the locations of these 10 residues are clearly shown on the surface of M1, and thus, they may have a direct relation to the rise in the optimum temperature. Previous studies have shown that the rigidity of surface residues is of great importance in the maintenance of protein thermostability. ,, Therefore, it is a common strategy to modify the surface amino acids for enhanced enzyme thermostability. , In addition, much protein-engineering research has revealed that besides the catalytic triads, the amino acids around the active site are crucial to the enzyme activity. , To achieve a thermostability-improved variant with minimum time and cost, three residues, Gly292, Phe269, and Gly264, were chosen as sites for point mutagenesis because (i) Gly292 possesses the highest b -factor value, indicating its flexibility in the structure, and (ii) Phe269 and Gly264 are close to the active site and located on the extruding loop, which might be of conformational importance for substrate binding (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In addition, much proteinengineering research has revealed that besides the catalytic triads, the amino acids around the active site are crucial to the enzyme activity. 33,34 To achieve a thermostability-improved variant with minimum time and cost, three residues, Gly292, Phe269, and Gly264, were chosen as sites for point mutagenesis because (i) Gly292 possesses the highest b-factor value, indicating its flexibility in the structure, and (ii) Phe269 and Gly264 are close to the active site and located on the The three amino acid residues chosen for subsequent site-directed mutagenesis are highlighted in bold. extruding loop, which might be of conformational importance for substrate binding (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The molecular modeling procedure was similar to that of our previous work. 28 Briefly, the models were constructed by SWISS-MODEL server 29−31 using the structure of DFA III-forming IFTase (BsIFTase, PDB ID: 2INV) 32 as a template (sequence identity = 48%) and verified by SAVES server (https:// services.mbi.ucla.edu/SAVES/). Moreover, the structural energy minimization was implemented by Discovery Studio package (Accelrys, San Diego, CA, U.S.A.).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The site-directed mutagenesis was implemented according to the TaKaRa MutantBEST Kit protocol, which can be found in our previous work. 28 The mutated residues can be divided into three groups. The residues in group I including G236, A257, G281, and A314 are located in the central tunnel formed by three identical subunits.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%